Synthesis, characterization and antitumor activity of palladium(II) complexes of imidazolidine-2-thione - de Moura, Thales R. [UNESP]; Cavalcanti, Sahra L. [UNESP]; de Godoy, Paulo R. D. V.; Sakamoto-Hojo, Elza T.; Rocha, Fillipe V.; de Almeida, Eduardo T.; Deflon, Victor M.; Mauro, Antonio E. [UNESP]; Netto, Adelino V. G. [UNESP] (Springer Nature, 2017)
Complexes of the type cis-[PdX2(imzt)(PPh3)] {imzt = imidazolidine-2-thione; PPh3 = triphenylphosphine; X = Cl (1), Br (2), I (3), SCN (4)} have been synthesized and characterized by elemental analyses, molar conductance, IR and 1H NMR spectroscopies. The complex 1·MeOH was obtained from the reaction of [PdCl2(CH3CN)2], imidazolidine-2-thione and triphenylphosphine in CHCl3/CH3OH. Complexes 2·MeOH, 3 and 4 were prepared by metathesis of the chlorido ligands in 1 with bromide, iodide and thiocyanate, respectively. Elemental analyses showed good agreement with the expected mononuclear compositions, while the molar conductivities of the complexes in DMF were consistent with their nonelectrolytic nature. NMR spectra confirmed coordination of the imidazolidine-2-thione and triphenylphosphine ligands. Single-crystal X-ray diffraction determination of 1·CH3OH showed that the coordination geometry around PdII is nearly square planar, with the chlorido ligands in a cis configuration. All four complexes have been tested in vitro by XTT assay for their cytotoxicity against human glioblastoma cell line (U87MG). The binding of 1 with guanosine was studied by 1H NMR spectroscopy, revealing that the coordination takes place via N7.